Immunization of mice with mycobacterial culture filtrate proteins. - Hubbard, R D (1992)
Culture filtrate proteins were obtained from Mycobacterium tuberculosis cultures after 7 days growth in Proskauer and Beck medium. The protein yield increased substantially to peak about the time the number of viable organisms reached its maximum level (day 8). Examination of the protein concentrate by SDS-PAGE revealed the presence of at least 12 separate protein bands varying from 10 to 90 kD. Mice were injected subcutaneously with 20 micrograms of M. tuberculosis culture filtrate (MTCF) protein suspended in saline or Freund's complete or incomplete adjuvant. The vaccinated mice were subjected to an aerogenic challenge with 10(3) colony-forming unit (CFU) M. tuberculosis Erdman and a significant reduction in the number of viable organisms was observed in the spleens and lungs determined over a 21-day period compared with age-matched normal controls. Mice immunized with the same culture filtrate proteins bound to nitrocellulose particles also showed some resistance to the virulent challenge, suggesting that individual antigens present in the culture filtrate were able to induce a protective T cell-mediated immune response in appropriately immunized mice.